Anatomopathological research in nineteenth-century Gdańsk – an outline of the problem - Szarszewski, Adam; Paluchowski, Piotr; Gulczyński, Jacek (Polish Journal of Pathology, 2019)
Between 1793 and 1914, there were many internationally recognised physicians active in Gdansk. Their scientific activities included, among other things, anatomopathological research, constituting a determinant of progress in medical sciences during this period. One of the most important people was Martin Heinrich Rathke (1793-1860). He is recognised as one of the founders of modern embryology. In Gdansk Rathke’s successor was Wilhelm Baum (1799-1883). Baum introduced compulsory post-mortem examinations in the city hospital even after the outbreak, and he was mentor to Theodor Billroth (1829-1894). The successor of Baum as the head of the city hospital was Emil Friedrich Götz (1806-1858). He took up an important topic, which was the consent of the family of the deceased to perform an autopsy. Furthermore, it described the gradual broadening of the scope of anatomopathological activities, consistent with the postulates of the first and second Viennese school, performed in Gdansk in the nineteenth century. However, a detailed analysis of the relationship between the discoveries of nineteenth-century medicine, especially in the field of pathological anatomy, and research carried out in Gdansk, remains in the sphere of research to be done.